Ethical Publication at the Nexus of Law, Language and Discourse - Robert J. Dickey (International Journal of Law, Language & Discourse, 2020)
The research area for law, language and discourse, an academic field with few dedicated scholarly journals (each interpreting the field differently) is overviewed. Ethical practices in research article publication, and the manuscript management and editorial process within the newly re-activated International Journal of Law, Language & Discourse are discussed and compared to various historic and contemporary practices in scholarly publication, including editorial and peer review, publisher duties, commercial journals, and publication strategies. “Predatory” journals are distinguished from reader-driven editorial practices.